Customer Intention to Use AI Technology on Beauty Industry - Pambudi, Yustikarani Julianti; Dwinata JS, I Putu Wahyu (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Artificial intelligence has emerged as one of the biggest disruptive technologies of the new era and will continue to evolve in the future. AI takes an important role in marketing processes, and the use of AI in marketing is massively increasing and can be easily found. Beauty industry is one of the industries where most companies develop their AI technology to attract customers. This innovation utilizes AI technology in providing solutions to problems related to makeup and/or skincare as experienced by the customers. This study aims to analyze the relationship between technology readiness, technology acceptance model and subjective norm as potential factors in encouraging the customer to use AI technology in the beauty industry. The data was collected using a google form questionnaire. The sampling technique for this research was purposive random sampling. A total of 155 responses were collated and only 127 responses are qualified with the criteria ‘ever using AI Technology in the beauty industry’. The results showed that while perceived usefulness had no significant impact on the intention to utilize AI technology, perceived comfort and subjective standards did. Additionally, the perceived advantages and ease of use are affected differently by each element of technology readiness.